Where's the water? - Wendy Dahl (EDIS)
This document addresses the risk of dehydration in frail older adults and the challenges of ensuring adequate water intake. It emphasizes the importance of both beverages and high-water-content foods in maintaining hydration. The article provides practical tips for encouraging fluid and food intake, such as consuming nutrient-rich beverages between meals and incorporating fruits and fruit juices into the diet. The aim is to prevent dehydration by promoting effective hydration strategies tailored to the needs of older adults. Original publication date May 2011.